2022
DOI: 10.3389/fmicb.2022.918134
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Patterns and Composition Traits of Soil Microbial Nitrogen-Metabolism Genes in the Robinia pseudoacacia Forests at a Regional Scale

Abstract: Microbial-driven processes related to the nitrogen-metabolism (N-metabolism) in soil are critical for ecosystem functioning and stability. There are spatial patterns of microbial-mediated nitrogen processes, but we still lack an overview of the soil N-metabolism genes of single nitrogen-fixing tree species pure forests at a regional scale. Here, we investigated the spatial variation and drivers of microbial N-metabolism genes in the rhizosphere soil of Robinia pseudoacacia on the Loess Plateau by metagenomic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…Microbial‐driven N metabolism in the soil is vital for sustaining forest ecosystem functioning and stability (Ku et al, 2022). The TN content in MCBP litter was higher than that in both BP and CP litters (Figure 1a), which was because of the highly diverse substrate and nutritional composition (Jia et al, 2021; Liu et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microbial‐driven N metabolism in the soil is vital for sustaining forest ecosystem functioning and stability (Ku et al, 2022). The TN content in MCBP litter was higher than that in both BP and CP litters (Figure 1a), which was because of the highly diverse substrate and nutritional composition (Jia et al, 2021; Liu et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…This enhancement was attributable to the similarity in microbial community composition and the role of functional microbes (Wang et al, 2021). Due to the similar litter substrate of BP and CP forests, resulting in the microbial community composition and a stronger association between N metabolism‐related enzymes and genes (Ku et al, 2022). The results showed that the substrate composition of pure litter (CP forest or BP forest) was a little different, and the microbial community structure was similar, reducing the consistency between functional enzymes and genes (Ding et al, 2023).…”
Section: Discussionmentioning
confidence: 99%